Kejadian Anemia Berdasarkan Status Gizi, Pengetahuan dan Pola Minum Teh pada Remaja Putri di Pondok Pesantren - Riyanto Riyanto; Gangsar Indah Lestari (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Anemia in adolescent girls is a common problem especially indeveloping countries. Purpose: The purpose of this study was to determine therelationship between factors of nutritional status, knowledge and patterns ofdrinking tea with the incidence of anemia in young women. Methods: The studydesign using a cross sectional study was carried out in November 2016. Thestudy population was young women in Tuma'ninah Yasin Islamic BoardingSchool in Metro City with a total sample of 69 taken with total populationtechniques. Data collection was done by examining peripheral blood, height,weight and distributing questionnaires. Data analysis was carried out in stages,namely univariate analysis and bivariate analysis using the chi square test.Results: The results of the analysis showed the incidence of anemia inadolescents amounted to 68.1%. Risk factors that increased the incidence ofanemia in adolescent boys, namely nutritional status or BMI (p = 0.32; POR =3.096) and knowledge (p = 0.050; POR = 3.083). Conclusions: Factors of pooror excessive nutritional status and lack of knowledge increase the incidence ofanemia in adolescent girls. The importance of health education efforts aboutanemia to young women to increase knowledge and consume Fe tablets,especially young women with good and poor nutritional status.